A REVIEW STUDY OF BIG DATA ANALYSIS TOOLS IN ACCOUNTING AUDITING (World Economics and Finance Bulletin, 2025)
How can big data analysis tools be adopted in accounting auditing in companies, based on the literature that focused on the importance of big data and accounting auditing, the study aimed to provide a comprehensive framework for big data analysis tools in accounting auditing, as the study provided a set of previous literature related to its topics and on the basis of the study reached several results represented in that there is an urgent need to update and develop the relationship between big data and accounting auditing for financial accountants, This contributes to improving the decision-making process, which began to enhance the capabilities of the advisory role of accountants, increase their abilities to think creatively and strategically, and provide the required assistance in making accounting decisions in line with the capabilities of companies and professional bodies to keep pace with future developments. The results also showed that there is an urgent need to transform the role of financial accountants by developing their capabilities in the advisory role of accountants on strategic thinking and providing critical assistance in making accounting decisions, and therefore it is important to update the accounting programs of companies in line with its capabilities in managing big data and enhancing the capabilities of auditors to use modern technologies adopted and preferred by customers to enhance the quality of auditing and provide added value to customers.